Propuesta de una metodología lean six sigma para el proceso de fabricación de quesos frescos en la empresa láctea Aprodemag. - Freire Quinatoa, Marco Eduardo (2020)
This research project consists of making a Lean Six Sigma methodological proposal for the manufacturing process of fresh cheeses in the dairy company APRODEMAG, which aims to improve the production line of fresh cheeses and the quality of the product. It begins with a bibliographical research and the characterization of its processes. The respective flow and process diagrams were prepared for the application of the DMAIC method. The methodology of the applied method has five phases, in the first one proceeded to collect information for the elaboration of the process flow diagram, Layout, and customer voice analysis survey. In the measure phase, the process was evaluated, determining the degree of maturity of the company, evaluation of machines, equipment and evaluation of personnel for the work. For this, the process analysis diagram, Pareto diagram, surveys aimed at staff, surveys based on parameters of the NTE INEN 1528: 2012, 9: 2012, 10: 2012 standards were applied. In the analyze phase, the Ishikawa diagram was applied and it was considered that the standardization of the process leads to the use of inappropriate methods, unnecessary times and poor use of additives for the production of fresh cheese, it was identified that the behavior of the staff is not adequate to carry out their work since they carry out their activities based on their experience, equipment in poor condition and lack of hygiene. In the improve phase, an improvement plan is proposed to standardize the process based on parameters of the NTE INEN standards, eliminate activities that do not generate added value to the process and improve the qualification of technical personnel. For the control phase, a control plan was carried out, where instructions were developed for the process that They must be monitored for compliance by the person in charge of production. The conclusions reached consider that the lack of procedures, controls and defined times do not comply with the adequate verification of the acceptability requirements of the NTE INEN standard. The proposal of the Lean Six Sigma methodology for the company can improve the cheese production system of the dairy company. The determination of the degree of maturity of the company allows justifying that it is at level 2 comprised in the range of 21%-40% compliance with the three INEN standards evaluated, 67% non-compliance and 33% compliance were determined. according to regulations.